Consolidative thoracic radiotherapy improves the prognosis of extensive stage small-cell lung cancer patients in the chemoimmunotherapy era: a multicenter retrospective analysis - Nan Yao; Shuai Li; Lingling Hu; Yixian Pei; Zhaohui Qin; Na Li; Shaodong Tong; Nan Zhang; Yuanhu Yao (Annals of Medicine)
Background For extensive-stage small cell lung cancer (ES-SCLC) with intrathoracic residuals after chemotherapy, the landmark CREST trial demonstrated the benefit of consolidative thoracic radiotherapy (cTRT). Yet the efficacy and safety of cTRT after chemoimmunotherapy for ES-SCLC remain largely unknown. This study aimed to assess the role of cTRT following chemoimmunotherapy in patients with ES-SCLC.Methods A retrospective analysis of ES-SCLC patients without disease progression after first-line chemoimmunotherapy was conducted between March 2019 and November 2021. Based on whether cTRT or not, patients were allocated to cTRT group or non-cTRT group. We evaluated efficacy by using the median overall survival (mOS) and progression-free survival (mPFS) times, and safety by measuring the incidence of adverse events.Results During this study, 72 patients with ES-SCLC were enrolled, with a median follow-up of 34.66 months. Twenty-nine patients received cTRT and 43 patients did not receive cTRT. Among the cTRT group and the non-cTRT group, the mPFS was 11.50 and 8.02 months, respectively, with a HR of 0.60 (95% CI 0.36–0.99, p = 0.043). The mOS in the cTRT group was also significantly longer than that in the non-cTRT group (28.68 months vs. 16.30 months, HR = 0.56, 95% CI 0.32–0.96, p = 0.033). Based on multivariate analysis, cTRT and cycles of immunotherapy ≥ 6 were independent factors affecting survival. There were no treatment-related deaths and most adverse events were grade 1–2.Conclusions This study suggests that the addition of cTRT to first-line chemoimmunotherapy significantly improves survival in ES-SCLC with well-tolerated toxicity.